The persistent power of human rights from commitment to compliance - Risse-Kappen, Thomas; Ropp, Stephen C.; Sikkink, Kathryn, 1955-; ProQuest (firma) (Cambridge : Cambridge University Press, 2013)
"The Power of Human Rights (published in 1999) was an innovative and influential contribution to the study of international human rights. At its centre was a 'spiral model' of human rights change which described the various socialisation processes through which international norms were internalised into the domestic practices of various authoritarian states during the Cold War years. The Persistent Power of Human Rights builds on these insights, extending its reach and analysis. It updates our understanding of the various casual mechanisms and conditions which produce behavioural compliance, and expands the range of rights-violating actors examined to include democratic and authoritarian Great Powers, corporations, guerilla groups and private actors. Using a unique blend of quantitative and qualitative research and theory, this book yields not only important new academic insights but also a host of useful lessons for policymakers and practitioners"--
Machine generated contents note: Part I. Introduction and Stock-Taking: 1. Introduction and overview Thomas Risse and Stephen C. Ropp; 2. The power of human rights a decade after: from euphoria to contestation? Anja Jetschke and Andrea Liese; 3. From ratification to compliance: quantitative evidence on the spiral model Beth A. Simmons; Part II. Conceptual and Methodological Issues: 4. Human rights in areas of limited statehood: the new agenda Tanja A. Börzel and Thomas Risse; 5. The 'compliance gap' and the efficacy of international human rights institutions Xinyuan Dai; 6. Social mechanisms to promote international human rights: complementary or contradictory? Ryan Goodman and Derek Jinks; Part III. From Ratification to Compliance: States Revisited: 7. The normative context of human rights criticism: treaty ratification and UN mechanisms Ann Marie Clark; 8. The US and torture: does the spiral model work? Kathryn Sikkink; 9. Resisting the power of human rights: the people's Republic of China Katrin Kinzelbach; 10. The 'Arab spring' and the spiral model: Tunisia and Morocco Vera van Hüllen; Part IV. From Commitment to Compliance: Companies, Rebel, Individuals: 11. Encouraging greater compliance: local networks and the United Nations global compact Wagaki Mwangi, Lothar Rieth and Hans Peter Schmitz; 12. Business and human rights: how corporate norm violators become norm entrepreneurs Nicole Deitelhoff and Klaus Dieter Wolf; 13. Taming of the warlords: commitment and compliance by armed opposition groups in civil wars Hyeran Jo and Katherine Bryant; 14. Changing hearts and minds: sexual politics and human rights Alison Brysk; 15. Conclusions Kathryn Sikkink and Thomas Risse.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Human rights; elektronické knihy; electronic books